IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PRILAKU POSITIF SISWA - Muhammad Muslim (UNISAN JURNAL, 2024)
Character education is seen as subordinate to noble morals. Historical facts confirm that the concept of character is profane. However, character education in Indonesia cannot be separated from religion, because the Unitary State of the Republic of Indonesia is based on Pancasila, especially, the First Principle, Belief in One Almighty God. The important things about the components that form character itself consist of: religiousness, honesty, tolerance, discipline. , hard work, creative, independent, democratic, curious, national spirit, love of the country, respect for achievements, friendly/communicative, love of peace, likes to read, cares about the environment, social care and responsibility. This research is a qualitative descriptive research. Research data was collected through observation, interviews and documentaries. Efforts made to overcome obstacles to developing positive interests, attitudes and behavior are by intensifying citizen discipline. Discipline is a factor that supports success in improving the quality of education, providing learning facilities and infrastructure Keywords: Implementation of Educational Management, Interests, Attitudes, Positive Behavior